Association of Serum Calcium with Resting Heart Rate and Blood Pressure in Healthy Adults - Zahid Habib Qureshi, Abida Jaffar, Khawar Younas, Bakhtawar Farooq, Khujasta Gul, Ejaz Hussain Sahu, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Calcium is a vital mineral with established roles in bone health, neuromuscular transmission, and cardiovascular regulation. Disturbances in calcium balance have been associated with hypertension and arrhythmias. However, the relationship between serum calcium and cardiovascular parameters in healthy adults remains underexplored. Objective: This study aimed to investigate the association of serum calcium with resting heart rate and blood pressure in healthy adult individuals. Methods: A cross-sectional study was conducted at the Department of Physiology, Multan Medical and Dental College, Multan, in collaboration with Nishtar Medical University (NMU), Multan, from March 2022 to March 2023. A total of 120 healthy adults aged 20–45 years were recruited. Participants with cardiovascular, renal, or metabolic diseases, or those on calcium supplements, were excluded. Serum calcium was estimated using the Arsenazo III colorimetric method. Resting heart rate and blood pressure were measured under standardized conditions. Data were analyzed using SPSS version 26. Correlations between serum calcium and cardiovascular parameters were assessed using Pearson’s correlation coefficient, with p < 0.05 considered statistically significant. Results: The mean serum calcium level was 9.2 ± 0.4 mg/dL. The mean systolic blood pressure was 118.4 ± 8.6 mmHg, diastolic blood pressure was 76.2 ± 6.3 mmHg, and resting heart rate was 74.5 ± 8.2 bpm. Serum calcium was inversely correlated with resting heart rate (r = –0.29, p = 0.002) and systolic blood pressure (r = –0.19, p = 0.030), while the correlation with diastolic blood pressure was not significant (r = –0.14, p = 0.080). Conclusion: Serum calcium is significantly associated with resting heart rate and modestly with systolic blood pressure in healthy adults, indicating a potential regulatory role of calcium in cardiovascular physiology. Keywords: Serum calcium, Resting heart rate, Blood pressure, Healthy adults, Cardiovascular physiology